Taxation of Non-Resident Entertainers and Sportsmen: The United Kingdom's Definition of Performance Income and How it Ought to be Measured - Alan Simpson (Washington University Global Studies Law Review, 2012)
This Note analyzes the U.K. approach to taxation of income earned for U.K. performances by foreign entertainers and athletes and agrees that the country of performance is the dispositive factor in determining which country is entitled to collect income tax on the endorsement income attributable to the performance. In Part II, this Note discusses the background of the relevant U.K. tax law. It reviews the U.K. court decisions in Agassi v. Robinson that led to the taxation of non-resident entertainers and athletes on endorsement contracts with companies that have no tax presence in the United Kingdom. Then, this Note discusses the U.K. acceptance of the substance-over-form tax doctrine after Agassi. In Part III, this Note evaluates the applicability of other sources of relevant international tax law, including the Organization for Economic Cooperation and Development (―OECD‖) and the United Kingdom—United States Bilateral Double Taxation Agreement. In Part IV, this Note recommends a definition for ―performance income‖ within the OECD Model Tax Convention on Capital and Investment. By working through the different possible types of compensation for the same service, this Note arrives at a definition consistent with income tax theory. The resulting definition parallels the same definition upheld by the U.K. courts. This Note also chooses a means for calculating the amount of income tax a country should charge from a performer‘s overall endorsement contract. Finally, the Note concludes in Part V.
Keywords: entertainment law; United Kingdom; taxation; sports law